The antimicrobial effect of calcium-doped titanium is activated by fibrinogen adsorption. Issue 7 (18th May 2022) - Cao, Huiliang; Dauben, Thomas J.; Helbing, Christian; Jia, Zhichao; Zhang, Yuechao; Huang, Moran; Müller, Lenka; Gu, Song; Zhang, Xiaoyuan; Qin, Hui; Martin, Karin; Bossert, Jörg; et al.
Abstract : Non-germicidal calcium doping is effective in exposing the antimicrobial action of human fibrinogen. Abstract : Directly targeting bacterial cells is the present paradigm for designing antimicrobial biomaterial surfaces and minimizing device-associated infections (DAIs); however, such pathways may create problems in tissue integration because materials that are toxic to bacteria can also be harmful to mammalian cells. Herein, we report an unexpected antimicrobial effect of calcium-doped titanium, which itself has no apparent killing effect on the growth of pathogenic bacteria ( Pseudomonas aeruginosa, Pa, ATCC 27853) while presenting strong inhibition efficiency on bacterial colonization after fibrinogen adsorption onto the material. Fine X-ray photoelectron spectroscopy and Fourier-transform infrared spectroscopy analyses reported calcium-dependent shifts of the binding energy in nitrogen and oxygen involved groups and wavenumbers in the amide I and II bands of the adsorbent fibrinogen, demonstrating that locally delivered calcium can react with the carboxy-terminal regions of the Aα chains and influence their interaction with the N-termini of the Bβ chains in fibrinogen. These reactions facilitate the exposure of the antimicrobial motifs of the protein, indicating the reason for the surprising antimicrobial efficacy of calcium-doped titanium. Since protein adsorption is an immediate intrinsic step during the implantation surgery, this finding may shift the present paradigm on the design of implantable antibacterial biomaterial surfaces.